Accesibilidad y su incidencia en el desarrollo turístico de La Poza de los Pachacos en la Parroquia Esmeraldas, cantón Montalvo - Secaira Fanís, Angelly Jamilex (2020)
The objective of this work is to analyze the importance of accessibility in the natural resource ¨Poza de los Pachacos¨, located in the rural parish La Esmeralda, Montalvo canton, it seeks to explain the basic concepts of accessibility in tourism, which will have a more specific focus on accessibility such as access routes and accessibility for disabled people. In this case study, three types of research were used: descriptive, exploratory and diagnostic. Descriptive research allowed to gather all the natural characteristics of the ¨Poza los Pachacos¨, the exploratory was based more on the search for projects in which accessibility has been key to the potentialization of a natural resource and finally the diagnosis allowed to analyze all the data collected to better understand the importance of accessibility in tourism. Surveys were also applied to the rural community of the Montalvo canton to measure their degree of knowledge about accessibility and how this could provide a great benefit to the use and optimization of the natural resource they have. Pleasant results were obtained, one of them the high interest of people in knowing how to enhance the Natural resource ¨La Poza de los Pachacos¨ and implement access roads around it.